Cleft hand classification and treatment: literature review - André Gustavo Pontes de Carvalho Pires; Marcela dos Santos Martins; João Carlos Nakamoto; Marcos Marcatto Abreu; Renato Novaes Oliveira; Arthur Perez Ferreira (Revista Brasileira de Cirurgia Plástica, 2022)
Cleft hand is a rare congenital deformity characterized by a longitudinal deficiency of the central rays of the hand, which may be associated with other malformations. Due to the wide spectrum of manifestations, the treatment is challenging. This study aims to present the most suitable classifications, surgical techniques and follow-up adopted according to the clinical manifestation. A search was performed in the databases Web of Science, PubMed, Scopus, Cochrane and Embase, descriptors and terms related to the hand anomaly in a typical cleft. Thirty-two articles were included and analyzed regarding the classification of the anomaly, classification of the severity of expression, surgical techniques and studies with information on the surgical intervention adopted for a cohort of patients. Considering that studies about cleft hand could be directly affected by embryological, genetic and molecular biology discoveries, different classifications have been described and several studies to complement existing surgical techniques have been found. Innovative studies are scarce. Standardization in the description of techniques and results, in addition to better quality research, could elucidate gaps that still exist around treatment options.